USE OF PROPHYLACTIC ANTIBIOTICS IN PATIENTS UNDERGOING CAESAREAN SECTION AT CUT MEUTIA GENERAL HOSPITAL, NORTH ACEH 2021-2022 - Yuziani; Virna Amelia Putri; Teuku Yudhi Iqbal (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Caesarean section is a surgical procedure to remove the fetus through an incision in the lining of the abdomen and uterus. Cesarean delivery is performed by considering clinical signs of the mother and fetus, such as placenta previa, abnormal location of the fetus, as well as different signs that may endanger the existence of the mother or embryo. According to the World Health Organization (WHO), the number of cesarean deliveries has increased, which is directly relative to the increase in the contamination rate of surgical wound infection (ILO). Prophylactic antibiotics are one of the prevention of surgical wound infection. The research method used is retrospective descriptive. The sampling technique in this research uses non-probability sampling, namely total sampling. The aftereffects of this review show that the use of prophylactic antibiotics in caesarean section patients, namely ceftriaxone 51.2% and cefotaxime 48.8%, the use of prophylactic antibiotics at the Cut Meutia Aceh General Hospital based on ASHP, the use of antibiotics ceftriaxone, cefotaxime, and reponem is 100% inappropriate and based on PPRA RSU Cut Meutia which is 100% compliant. The aftereffects of this study presumed that the utilization of anti-toxins based on ASHP is not appropriate and based on PPRA Cut Meutia Hospital is appropriate.